Effect of non-rubber components on the crosslinking structure and thermo-oxidative degradation of natural rubber - Wang, Mengyu; Wang, Rui; Chen, Xiangfei; Kong, Yiran; Huang, Yajiang; Lv, Yadong; Li, Guangxian (Polymer degradation and stability, 2022)
•As a natural antioxidant, NRCs improved the thermo-oxidative stability of NR.•NRCs promoted the formation of mono- and disulfide bonds during vulcanization.•More monosulfide bonds were formed during the aging of vulcanized SHANR.•SHANR showed high thermal/mechanical stability against aging. Non-rubber components (NRCs) in natural rubber (NR), including proteins, phospholipids, fatty acids, etc., determine to a large extent the structure and properties of NR. In this study, the effects of NRCs on the network structure and thermo-oxidative aging behavior of unvulcanized and vulcanized NR were investigated. NRCs were found to form physically crosslinked networks in the unvulcanized NR and acted as a natural antioxidant to scavenge free radicals, which contributed to improved thermo-oxidative stability of the unvulcanized NR. Swell analysis, chemical probe analysis (DPPH), and XPS results showed that the NRCs accelerated the vulcanization reaction and increased the crosslink density, and promoted the formation of more mono- and disulfide bonds during vulcanization. When aged at high temperatures, more monosulfide bonds were formed in the vulcanized rubber with high contents of NRCs by cleaving and rearranging the poly- and disulfide bonds. NRCs were also found to increase the activation energy of thermal degradation and led to the better mechanical stability of vulcanized NR against thermal oxidation.